TRANSLATIONAL DIVERGENCES IN THE GEOGRAPHY AND THEONYMY OF THE AVESTA: A COMPARATIVE STUDY OF THE FIRST FARGARD OF THE VIDEVDAT (American Journal of Research in Humanities and Social Sciences, 2026)
This article focuses on the comparative philological and historical analysis of the first fargard of the Videvdat (Vendidad) section of the "Avesta." It examines structural discrepancies, theonymic variations, and geographical localizations across three major modern translations: Asqar Mahkam’s Uzbek edition, James Darmesteter’s English translation, and I.M. Steblin-Kamensky’s Russian translation. Through meticulous textual mapping, the study illuminates how variations in verse division, different renderings of ancient deities and heroes (e.g., Angra Mainyu vs. Ahriman, Thraetaona vs. Faridun), and divergent accounts of Ahriman’s adversarial creations distort historical and geographic interpretations. The findings emphasize the need for unified source-critical methods when analyzing ancient Central Asian texts to avoid unreliable historical conclusions.